Secular Stagnation: Insights from a New Keynesian Model with Hysteresis Effects - Bas van Aarle (Center for Economic Studies and ifo Institute (CESifo), 2016)
To analyse the most important aspects of the Secular Stagnation hypothesis, this paper considers the effects of hysteresis in potential output in a New-Keynesian model that is extended with endogenous potential output. To do so, a number of simulations of relevant scenarios is undertaken. It is demonstrated that extending the New-Keynesian model with hysteresis has a number of crucial implications for macro-economic adjustment and macro-economic management. It is indicated how the model can contribute to a better understanding of a number of important elements of the Secular Stagnation hypothesis.
Keywords: E31; E43; E62; H62; 330; potential output hysteresis; monetary policy; fiscal policy